2016
DOI: 10.1002/nau.22979
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of Peristeen® transanal irrigation system with the validated neurogenic bowel dysfunction score sheet in the pediatric population

Abstract: The Peristeen® transanal irrigation system provides a significant reduction in NBoDS scores in pediatric patients with NBD. Peristeen® should be considered when other conservative bowel management options have been unsuccessful. Neurourol. Urodynam. 36:632-635, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Quality of life, associated with bowel dysfunction, was evaluated in 12 studies. In eight, enhanced quality of life was seen (significant results) (Ausili et al, 2010; Choi et al, 2015; Christensen et al, 2006,2008; Del Popolo et al, 2008; Kelly, Dorgalli, McLorie, & Khoury, 2017; Kim et al, 2013; Loftus et al, 2012). However, King et al (2017) reported no significant difference among users when compared with those no longer using TAI.…”
Section: Resultsmentioning
confidence: 99%
“…Quality of life, associated with bowel dysfunction, was evaluated in 12 studies. In eight, enhanced quality of life was seen (significant results) (Ausili et al, 2010; Choi et al, 2015; Christensen et al, 2006,2008; Del Popolo et al, 2008; Kelly, Dorgalli, McLorie, & Khoury, 2017; Kim et al, 2013; Loftus et al, 2012). However, King et al (2017) reported no significant difference among users when compared with those no longer using TAI.…”
Section: Resultsmentioning
confidence: 99%
“…In children with NBD who do not respond to conservative or medical treatments, TAI is an increasingly accepted treatment [13]. There are studies demonstrating improved QoL and outcomes with children utilizing TAI for functional incontinence and functional constipation, and some authors recommend TAI should be mandated prior to considering any invasive surgical intervention [146]. A summary publication of TAI use in children incorporated a literature review comprising 27 studies with 1040 patients whose average age was 8 years old [13].…”
Section: Transanal Irrigationmentioning
confidence: 99%
“…The SNM procedure has been described in detail previously [15]. The procedure is divided into two stages.…”
Section: Snm Proceduresmentioning
confidence: 99%
“…The testing phase does not usually exceed 4 weeks. Under normal conditions, success of SNM is usually defined as at least a 50% improvement in the number of voids, the number of episodes of urgency and incontinence in patients with overactive bladder, voided volume, number of catheterizations and catheterized volume in patients with urinary retention [15]. If the test was considered positive, a pulse generator (InterStim model 3023, Medtronic Inc.) was implanted and connected to the tined lead inserted during the testing phase.…”
Section: Snm Proceduresmentioning
confidence: 99%
See 1 more Smart Citation